Incremental cost-utility of sevelamer relative to calcium carbonate for treatment of hyperphosphatemia among pre-dialysis chronic kidney disease patients - Nguyen H.V. (BioMed Central Ltd., 2018)
10.1186/s12882-016-0256-0